A decade of transitioning malaysia toward a high-solar pv energy penetration nation - Husain A.A.F.; Phesal M.H.A.; Kadir M.Z.A.A.; Amirulddin U.A.U.; Junaidi A.H.J. (MDPI, 2023)
alternative energy; developing world; electricity industry; installation; knowledge; photovoltaic system; spatiotemporal analysis; Malaysia